Pembangunan sistem pangkalan data marin untuk bantuan navigasi di pelabuhan - Ghazali, Noorzalianee (2008)
Maritime transportation has grown rapidly and thus the need for new or upgrading of the existing ports is an ongoing development. The main weakness for many ports is the unability to manipulate data in such an effective manner through information integration from various source. This limitation is critical since the reputation of the ports is mainly driven by the efficiency of information supporting the port operation. Information in various format and scale owned by various agency have the tendency to be misinterpretated due to the discrepancy in coordinate system, symbol, colour and object presentation. This is made worse by inconsistent data accuracy among these agency. Apart from inconsistent data accuracy, miscommunication between agency also cause data not to be fully updated. Thus it will become obstacle for smooth operation at ports since important parameter for simulation or prediction are not accurate. Real world modelling by spatial and attribute data representation in database enable manual interpretation to be done alongside the testing of database capability to support user in technical maintenance job as well as monitoring the port area. Data selection and collection based on data functionality has been used to develop additional application to support user with the help of perfect data model. The model has contribute to application development through data interpretation on series of two dimension (2D ) analysis and and 3D analytical series. Total automation field test and real time result has given new dimension to field procedure and concurrently increase quality of work and reduce cost and time by maximising users ability to navigation in port area especially at stringent area when ship about to berth and departure.